The World of the Bible. Translated by Sierd Woudstra - Ridderbos, H. N.; Reiling, J.; Oosterhoff, B. J.; Mulder, M. J. (1986)
van der Woude, A. S. (General Editor); Translated from the Dutch De Wereld van de Bijbel. Kampen 1981. J. H. Kok.